2018
DOI: 10.1111/bju.14416
|View full text |Cite
|
Sign up to set email alerts
|

Does mirabegron relieve ureteric stent‐related discomfort? A prospective, randomized, multicentre study

Abstract: The use of 50 mg mirabegron once daily has the potential to reduce ureteric stent-related discomfort. Prospective larger-scale, placebo-controlled studies are warranted to further evaluate the beneficial effects of mirabegron on stent-related symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(69 citation statements)
references
References 29 publications
3
64
0
2
Order By: Relevance
“…In addition, it has been reported to be an effective and safe medical expulsive treatment agent for the reduction of distal ureteral stones with a low rate of side effects [4,14]. Mirabegron reduces the disturbing symptoms related to stents by dilatation of the ureter and decreasing intraluminal pressure [15]. These effects led to the idea that the use of mirabegron during UAS placement might provide convenience to the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported to be an effective and safe medical expulsive treatment agent for the reduction of distal ureteral stones with a low rate of side effects [4,14]. Mirabegron reduces the disturbing symptoms related to stents by dilatation of the ureter and decreasing intraluminal pressure [15]. These effects led to the idea that the use of mirabegron during UAS placement might provide convenience to the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that 50 mg Mirabegron had the potential to reduce ureteric stent-related discomfort. 85 A large RCT by Ragab et al highlighted that patients with both pregabalin and solifenacin had better USSQ scores and pregabalin alone was well tolerated and safe in patients with stent-related symptoms. 86,87 A small study by Tharwat et al showed that sildenafil was tolerated in men with ureteral-related symptoms.…”
Section: Beta-3 Adrenergic Agonistsmentioning
confidence: 99%
“…The authors concluded that 50 mg Mirabegron had the potential to reduce ureteric stent-related discomfort. 85 …”
Section: Pharmacological Strategies To Improve Stent-related Symptomsmentioning
confidence: 99%
“…In a study by Lennon et al, a significant increase in SRS was attributed to ureteral stent firmness [12]. The magnitude of stent firmness is reliant on the material ureteral stents are composed of.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics include the length of the stent [5], stent positioning [6], changing bladder pig tail to loop type [7], use of stents with special coatings [8], and composition of biomaterials of different firmness [9]. Additionally, the use of alpha1-and choline blockers, with their combinations [10], nonsteroidal antiinflammatory drugs [11] and mirabegron [12] have also been studied in order to reduce intensity of SRS experienced by patients. Despite this, patients with indwelling stents continue to experience SRS [13].…”
Section: Introductionmentioning
confidence: 99%